Anti-nephrotoxic activity of aqueous extract of polyherbal mixture against renal toxicity induced by paracetamol in Wistar albino rats - MICHAEL SUNDAY ABU; RUKAIYAT LAWAL MASHI; JAMILA YAHAYA LAWAL; OYEBISI SUNDAY SAMUEL (Nusantara Bioscience, 2023)
Abstract. Abu MS, Mashi RL, Lawal JY, Samuel OS. 2023. Anti-nephrotoxic activity of aqueous extract of polyherbal mixture against renal toxicity induced by paracetamol in Wistar albino rats. Nusantara Bioscience 15: 112-117. Medicinal plant materials as sources of therapeutic compounds continue to play an important role in maintaining human health for ages. This study investigated the effect of polyherbal extract (Carica papaya L., Allium sativum L., Curcuma longa L., and Azadirachta indica A.Juss.) on urea, creatinine, sodium ion, potassium ion, and chloride ion concentrations, and body weight of Wistar rats intoxicated with paracetamol. Thirty Wistar rats were randomly distributed into six groups, with five in each group. Group 1 is the normal control group; Group 2 is the negative control group (paracetamol-induced but untreated); Group 3 received 140 mgkg-1 of silymarin; Groups 4, 5, and 6 received 100, 300, and 500 mgkg-1 body of the aqueous polyherbal extract respectively for seven days. Therefore, the blood samples were collected and evaluated for creatinine, urea, sodium, potassium, and chloride ions concentrations to measure kidney function. The results revealed that the aqueous extract of the polyherbal mixture significantly (p<0.05) ameliorated the kidney function test parameters that were analyzed by lowering their concentrations previously elevated by the paracetamol intoxication comparable with the normal control rats. Therefore, it can be concluded that the polyherbal mixture extract expressed an anti-nephrotoxic effect against renal toxicity induced by paracetamol in Wistar albino rats.